1.2k views
6 votes
Using ƒ(x) = 2x + 7 and g(x) = x − 3, find ƒ(g(-2)).

Using ƒ(x) = 2x + 7 and g(x) = x − 3, find ƒ(g(-2)).-example-1
User Latifa
by
4.6k points

1 Answer

10 votes

Answer:

We conclude that:

f(g(-2)) = -3

Explanation:

Given

  • f(x) = 2x + 7
  • g(x) = x-3

To determine

  • f(g(-2)) = ?

In order to determine f(g(-2)), first we need to determine g(-2)

so substituting x = -2 in g(x) = x-3

g(-2) = -2 - 3

= -5

Thus,

f(g(-2)) = f(-5)

now substitute x = -5 in the function f(x) = 2x+7

f(x) = 2x+7

f(-5) = 2(-5) + 7

f(-5) = -10 + 7

f(-5) = -3

so

f(g(-2)) = f(-5) = -3

Therefore, we conclude that:

f(g(-2)) = -3

User MrMage
by
4.9k points